Biochars in soils: towards the required level of scientific understanding. Issue 2 (3rd April 2017) - Tammeorg, Priit; Bastos, Ana Catarina; Jeffery, Simon; Rees, Frédéric; Kern, Jürgen; Graber, Ellen R.; Ventura, Maurizio; Kibblewhite, Mark; Amaro, António; Budai, Alice; Cordovil, Cláudia M. d. S.; Domene, Xavier; et al.
Abstract: Key priorities in biochar research for future guidance of sustainable policy development have been identified by expert assessment within the COST Action TD1107. The current level of scientific understanding (LOSU) regarding the consequences of biochar application to soil were explored. Five broad thematic areas of biochar research were addressed: soil biodiversity and ecotoxicology, soil organic matter and greenhouse gas (GHG) emissions, soil physical properties, nutrient cycles and crop production, and soil remediation. The highest future research priorities regarding biochar's effects in soils were: functional redundancy within soil microbial communities, bioavailability of biochar's contaminants to soil biota, soil organic matter stability, GHG emissions, soil formation, soil hydrology, nutrient cycling due to microbial priming as well as altered rhizosphere ecology, and soil pH buffering capacity. Methodological and other constraints to achieve the required LOSU are discussed and options for efficient progress of biochar research and sustainable application to soil are presented.